Development of nanotechnology of fine-dispersed additives with the use of cryogenic mechanical modification - Павлюк, Раїса Юріївна; Погарська, Вікторія Вадимівна; Бессараб, Олександр Семенович; Балабай, Катерина Сергіївна; Борисова, Аліна Олексіївна; Лосєва, Світлана Михайлівна (Eastern-European Journal of Enterprise Technologies, 2014)
Nanotechnologies of fine-dispersed additives based on topinambour in the form of frozen puree and freeze-dried powder with the use of cryogenic mechanical modification particularly cryogenic "shock" freezing and low-temperature mechanical grinding is proposed and developed. A unique new technology allows to get additives and food products containing record amount of fructose in free condition: 50-55% of inulin is transformed into easily digestible fructose in free condition that reduces glycemic index and the immune system reinforcement. Simultaneously cellulose and protein destruction and degradation occur: 50% of cellulose is transformed into its monomers – glucose and 50% of protein is destroyed to separate free amino acids. It is also established that mechanical and cryogenic destruction, accompanying "shock" freezing and fine-dispersed grinding of topinambour, allows both to save all biologically active supplements such as phenolic compounds, ascorbic acid, tannins etc. and free-out them from the bound complexes with biopolymers or associates transforming them to free condition (their amount increases 1,7-2,2 times comparing with the original raw materials). It allows to cook product with new chemical composition and excellent consumer properties.